DISCOURSE, PERFORMATIVITY AND EMERGENCE OF THE SUBJECT: AN APPROACH FROM POST-STRUCTURALISM - Morales, Maria Virginia (Athenea digital, 2014)
The study of the structures of meaning and the formation of hegemonies play a leading role in post-structuralist theories of politics. In the present paper addresses a series of ontological aspects of these theories from the reflection of the conditions of emergence of systems of meaning, the way these systems are built and how they constitute the social field and the subjects are positioned in it. Thus, motivates me to analyze some of the main epistemological categories that I consider central to any post-structuralist research, namely, discourse, performativity and subject. In short, this paper has two purposes: to investigate ontological aspects that underlie the theories in question, while beginning to develop a conceptual framework from which to address the emergency conditions of the discursive structures that shape and give meaning and social subjects. Adapted from the source document.